2014 IEEE 2nd International Conference on Emerging Electronics (ICEE) 2014
DOI: 10.1109/icemelec.2014.7151181
|View full text |Cite
|
Sign up to set email alerts
|

Microwave pulse-assisted wet chemical synthesis of ZnO nanoparticles with excellent UV emission

Abstract: ZnO nanoparticles (ZNPs) were synthesized by wet chemical method using poly vinyl alcohol (PVA) templates. Uniform growth, high yield and excellent optical properties were observed in ZNPs synthesized under pulsed microwave irradiation (PMW). Moreover the dangling bonds of ZNPs prepared under PMW were passivated more effectively than in samples prepared without it. Strong UV emission peaks at ~ 360 nm and 380 nm, along with a feeble defect-related visible emission peak at ~ 465 nm, were observed in the room te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…So there is a quest for new, simpler and efficient synthetic routes with alternative solvents. Present study focuses on synthesis of size controlled CdTe QDs through a fast and facile MW [17] aided wet chemical route. Glutathione (GSH)-capped CdTe QDs (GSH-CdTe) were synthesized under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…So there is a quest for new, simpler and efficient synthetic routes with alternative solvents. Present study focuses on synthesis of size controlled CdTe QDs through a fast and facile MW [17] aided wet chemical route. Glutathione (GSH)-capped CdTe QDs (GSH-CdTe) were synthesized under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1. The basic growth unit is [Zn(OH) 4 ] 2-in the solution-based method to grow ZnO nano forms by the reaction of Zn+ ions with the OH-ions [8] further it is changed in ZnO. The crystal habit of wurtzite ZnO exhibits well-defined crystallographic faces such as polar-terminated (0001) and non-polar low-symmetry (1010).…”
Section: Znomentioning
confidence: 99%
“…Thus, the It can be observed that the morphology significantly depends on the molarity of precursor solution. Fig.2 2 and growth unit Zn (OH) 4 2-in aggregated form. The growth units of ZnO arrange themselves in water solvent, in presence of microwave irradiation pulse.…”
Section: Znomentioning
confidence: 99%
See 2 more Smart Citations